Determinants of Inclusive Economic Development: A Fixed Effect Model Approach - Anita, Rossy Dwi; Udjianto, Didit Welly (JAMPE (Journal of Asset Management and Public Economy), 2024)
The implementation of development in Indonesia faces challenges and obstacles along with the dynamics of community life and changes in the global constellation. The economic development model that has been applied only encourages economic growth, resulting in social exclusion in the form of poverty, unemployment and social inequality. This study aims to estimate the factors that influence inclusive economic development in Indonesia. The data used comes from 34 provinces in the period 2015-2022. This research contributes to economic development in the form of inclusive economic development, the use of IEDI as a value that shows the level of inclusiveness of Indonesia's development, and contributes to the determinants of IEDI. The model used is FEM with the results showing that the variable open unemployment rate has a negative and significant effect. The rate of GRDP, and HDI has a positive and significant effect on inclusive economic development. The number of poor people insignificant effect. This is based on the trickle-down effect theory which explains that the progress obtained by a group of people automatically trickles down so that it will create jobs. In the end, it will foster an equitable distribution of the results of economic growth. Since economic growth is an indicator of economic development, such changes will affect the number of poor people in the long run.